Pengaruh Kebijakan Dividen, Nilai Pasar, Pertumbuhan Perusahaan, dan Volume Perdagangan Terhadap Harga Saham - Apriliana, Liana (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
This study aims to obtain empirical evidence regarding the effect of dividend policy, market value, company growth, and trading volume on stock prices. This type of research is quantitative research. The population in this study are banking sub-sector companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The sampling technique used in this study was obtained using the method purposive sampling. The total population in this study were 41 companies and 11 companies that met the sample criteria. The analytical method used in this research is panel data regression analysis with the help of an applicationEviews 12. The results of this study indicate that simultaneously dividend policy, market value, company growth, and trading volume affect stock prices. While partially the dividend policy and company growth have no effect on stock prices, market value and trading volume have an effect on stock prices.